Nudging the adoption of fuel-efficient vehicles: Evidence from a stated choice experiment in Nepal - Massimo Filippini; Nilkanth Kumar; Suchita Srinivasan (ETH Zurich, CER-ETH - Center of Economic Research, 2020)
Addressing hazardous levels of air pollution in densely-populated cities in emerging countries requires concerted efforts to reduce fossil fuel use, especially in the transport sector. Given that motorcycles comprise almost 80% of vehicle sales in Nepal, a viable alternative to reduce air pollution is driving more fuel-efficient electric alternatives. However, their adoption has been limited due to a gamut of market failures and behavioral anomalies. In this study, we collect rich data on preferences, socio-economic factors and biases of more than 2,000 potential motorcycle buyers in the Kathmandu valley in Nepal. Using a stated choice experiment with randomized information treatments, we evaluate the role of specific behavioral anomalies in determining the stated-preference of consumers on whether they would be willing to buy an electric motorcycle. We find evidence to suggest that cognitive/skills limitations, framing of information, and the affect heuristic play a role in determining the stated-preference of respondents. In particular, displaying qualitative information on the air pollution impact of their choices, and "priming" them through impactful photographs and texts could have a positive effect. Furthermore, the results also hint at the importance of gender, health status and cognitive skills in determining the effectiveness of these nudges in promoting the adoption of electric alternatives. Implications of this study relate to policy choice in settings similar to Kathmandu, where fuel-inefficient vehicles are preferred and widely used, and the negative externalities due to air pollution are very stark.
Keywords: D1; D8; Q4; Q5; 330; Market failures; Behavioral anomalies; Electric vehicles; Stated-choice experiment; Nepal